MEMBANGKITKAN GENERASI MUDA BERINTEGRITAS SERTA MENINGKATKAN POLA HIDUP SEHAT BEBAS DARI NAPZA PADA SISWA (I) SMA NEGERI 13 TAKALAR - Hasnawati S; Saskia Amelia; Jilan Syarah Luckyta Sari; Faishal Mustafa (COVIT (Community Service of Health), 2022)
NAPZA stands for Narcotics, Psychotropics, and other Addictive Substances. The use of drugs is very dangerous for both mental and physical health of users. Drug users are at risk for impaired brain development, suicide and depression, memory loss, high risk for sexual behavior, addiction, impaired decision making, poor academic performance, violence, and motor vehicle accidents. Adolescent development is very vulnerable to the influence of the environment in everyday life. The transition period of adolescent development from children to adults is not only about age but also involves biological, cognitive, and socio-emotional changes. Changes in children's behavior, some in a positive direction and some in a negative direction. One of the negative behaviors is teenagers with habitual behavior of consuming alcohol. The many impacts experienced by drug abusers so that a treatment program is needed for those who have experienced drug abuse and anticipation for those who have not been entangled in using drugs, especially from the age of teenagers/students. This service is carried out on 12th grade high school students who are students of transition age to adolescence because in the next 3 years they will move into the teenage level. Through this service activity, it is expected to be able to provide understanding to SMAN 13 Takalar students about the dangers suffered by drug abuse, types and types of narcotics and how to overcome them. The method used provides a presentation of the correct understanding of drugs, discussions, questions and answers, the dangers and effective steps so that students can suppress negative behavior and abuse of drugs and harmful additives. In the activities carried out for approximately 4 hours, the children were very enthusiastic and became aware of the definition, forms, uses and dangers of drugs and committed not to use them in the future. Keywords: Education, prevention, deviant behavior